2016
DOI: 10.1515/helmin-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin in Trichinella pseudospiralis: An immunocytochemical study

Abstract: SummaryThis is the fi rst report on the presence and localization of the neurotransmitter serotonin (5-HT) in the nervous system of the nematode Trichinella pseudospiralis, the causative agent of trichinellosis. The orientation of the 5-HT-immunoreactive (5-HT-IR) nerve cells in the adult worm is described. In the anterior region of the worm 5-HT-IR occurs in 7 neurons. Longitudinal nerve cords extend posteriorly from the anterior end. They are connected by transverse commissures. The vulval area is intensivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(45 reference statements)
1
0
0
Order By: Relevance
“…The results from the analysis of the numbers of entities and reactions follow similar patterns and confirmed previous considerations (Figure 4B). These findings are in agreement with widely published literature, where it is reported that the neurotransmitter serotonin has a very early origin and is expected to be conserved throughout metazoans, as well as prokaryotes and plants, playing a variety of critical roles (Campos et al, 2016; Pilowsky, 2018; Romero‐Reyes et al, 2021; Terenina et al, 2016; Turlejski, 1996). The full output is reported in Supporting Information 3, Case Study 3.…”
Section: Resultssupporting
confidence: 91%
“…The results from the analysis of the numbers of entities and reactions follow similar patterns and confirmed previous considerations (Figure 4B). These findings are in agreement with widely published literature, where it is reported that the neurotransmitter serotonin has a very early origin and is expected to be conserved throughout metazoans, as well as prokaryotes and plants, playing a variety of critical roles (Campos et al, 2016; Pilowsky, 2018; Romero‐Reyes et al, 2021; Terenina et al, 2016; Turlejski, 1996). The full output is reported in Supporting Information 3, Case Study 3.…”
Section: Resultssupporting
confidence: 91%